It girl : a novel - Pataki, Allison (Ballantine Books, 2026)
"At the dawn of the twentieth century, New York's streets teem with change: electricity, automobiles, the brash young President Teddy Roosevelt--and the It Girls. As artists' muses and working models, these independent young women soar to stardom not because of their pedigrees or inherited wealth, but because of their talent, charisma, and irresistible beauty. Pop culture is born, and in a world alight with Mr. Edison's new bulbs, no one shines brighter than America's sweetheart, Evelyn Talbot. But the journey to stardom is not simple or straight. While working as a shopgirl, the young Evelyn is recruited as a studio model and soon catches the eye of the preeminent artists of the age. When Broadway comes calling, Evelyn solidifies her status as the first self-made American female celebrity: the iconic Gibson Girl, the most sought-after figure and face of her time. Enter a parade of powerful and power-hungry men, from world-famous architect Stanley Pierce, the visionary behind Manhattan's mansions and iconic landmarks, to Hal Thorne, the shockingly wealthy railroad heir and premier "playboy" of high society. Each man promises comfort, glamour, security--even love. But fame and fortune are cruel teachers, and Evelyn learns that the only person she can rely on is herself. When Evelyn finds herself at the center of a murder of passion declared "the Crime of the Century," she is blamed for the acts of the men in her life. In the media frenzy that spirals around her, Evelyn realizes that to survive, she will have to write her own ending. But can this artists' muse turned showgirl pull off the greatest act of her life?"--